Verb Go Combinations in Perspective English Linguistics and Culture - DEDEN NOVAN SETIAWAN NUGRAHA (SAMPURASUN, 2016)
Language and culture are both integral parts of human life. Humans use language to express their feelings, and to communicate to each other. To support the processs of communication language must be able to represent ideas of speakers and be understood by the hearers. Linguistics is the study of languge. The part of linguistics that is concerned with the structure of language is divided into a number of subfields: syntax and semantics. Syntax is the system of rules and categories that underlies sentence formation in human language, meanwhile semantics is the study of meaning in human languge. Because language is such a central feature of being a human, linguistics has connections with many other disciplines in the humanities like culture. Based on Sapir-Whorf Hypothesis (Sapir, 1929); (a). Language influences thought and culture; (b). Language and culture influence each other. This study aims to investigate syntactic categories combined to the verb go and to analyze the meaning of the verb go after being combined with the complements. The data itself is taken from the British National Corpus (BNC). The results of the article indicate that there is a very close relationship between language and culture. That is, culture has a direct effect on language. Language and culture are closely correlated. Based on the analysis, the verb go can be combined with nouns, verbs, adjectives, adverbs, verbs-ing and past participles. In the case of semantic analysis there are two categories of meaning of the verb go combinations: dynamic verb indicates moving away from something or causing something to move or to happen; and stative verb which shows the meaning of steady state with no internal changes or phases. Most of the verb go combinations have generates new meaning, that is idiomatic meaning.